(untitled) (Journal of Hama University, 2020)
An experimental feeding trial was conducted to visualize the impact of dietary Turmeric (Curcuma longa) and/or Cumin (Cyminum cyminum) fortification at a rate of 3 Kg/ton in broiler diets on growth performance. Consequently, total of (240) one-day old chicks (Cobb 500) was randomly assigned into 4 equal groups each of three replicates. The first group was fed on corn- soya bean based basal diets (starter- grower- finisher) covering the nutrient requirements according to the recommendation of the breed manual without any supplementation and served as control group (G1). The second group (G2) was fed on the basal diets fortified with Cumin powder. The third group (G3) was fed on the basal diets and fortified with Turmeric powder at the same inclusion rate. Meanwhile the diets of the fourth group (G4) were fortified with both additives at the same inclusion rate for each additive. The results revealed significant (P < 0.05) positive effects of Turmeric and Cumin addition either separately or combined together (G2, G3 and G4) on most of growth performance traits. None of the examined serum parameters seemed to be affected by different dietary fortification. The highest (GSH), (GPx) and superoxide dismutase and lowest significant (MDA) levels were observed in the bird supplemented with turmeric and/or cumin in comparison to the control group, a situation that indicated a positive impact of both additives either added alone or in combination on antioxidant defense mechanisms. Results also indicated significant positive effects on most of carcass traits. In addition, histo-morphological picture showed normal histo-morphological structure without any histo- pathological alteration of the hepatocytes. It could be concluded that the use of both Turmeric and/or Cumin either alone or in combination at the aforementioned levels and route of administration had positive effects on growth performance, carcass traits, and antioxidant status of broiler chickens, although they didn’t affect serum biomarkers and gut morphology a situation